Surgical treatment of giant chordoma in the thoracic spine combining thoracoscopic and posterior spinal surgery: A case report. Issue 35 (August 2019) - Liu, Shuzhong; Zhou, Xi; Song, An; Huo, Zhen; Yao, Siyuan; Wang, Yipeng; Liu, Yong
Abstract: Rationale: Giant thoracic chordoma is a highly unusual disease with no standard curative managements yet. The objective of this study is to report a very rare case of giant thoracic chordoma successfully operated by combination of thoracoscopic surgery together with posterior spinal surgery. The management of these unique cases has yet to be well-documented. Patient concerns: A 64-year-old man presented with a 4-month history of continuous and progressive back pain. The patient, who had been diagnosed of sacral chordoma for 2 years, received surgical treatment of posterior sacral tumor resection and instrumentation. A lytic, expanding lesion of the T5 and T6 vertebral and paraspinal region with mild epidural spinal cord compression was identified. Diagnosis: MRI of spine and PET/CT showed spinal cord compression secondary to the epidural component of the T5 and T6 mass, with increased metastatic marrow infiltration of the left T5 and T6 vertebral and paravertebral region, which presented as a solid tumor. Postoperative pathology confirmed the diagnosis of thoracic chordoma. Interventions: The patient underwent 1-stage thoracoscopic release of vertebral and paravertebral tumors, posterior resection of T5-T6 vertebral and paravertebral tumors, T4-T7 spinal canal decompression, and T2-T9 pedicle screw fixation procedure via a posterior approach. Outcomes: The patient's neurological deficits improved significantly after the surgery, and the postoperative period was uneventful at the 3-month and 6-month follow-up visit. There were no other complications associated with the operation during the follow-up period. Lessons: Taken together, the lesion's clinical features, imaging results, and pathological characteristics are unique. Combined efforts of specialists from orthopedics, thoracic surgery, neurosurgery, and medical oncology led to the successful diagnosis and management of this patient. Giant thoracic chordoma, although rare, should be part of the differential diagnosis when the patient has a history of sacral chordoma and presents with back pain and radiculopathy. We recommend the posterior approach for spinal decompression of the giant thoracic chordoma when the tumor has caused neurological deficits. One-stage thoracoscopic release or resection of vertebral and paravertebral tumor is also a good choice for surgical treatment.